The use of blended learning to improve health professionals’ communication skills: a literature review - Cappi, Valentina; Artioli, Giovanna; Ninfa, Erika; Ferrari, Silvia; Guarnieri, Maria Cristina; Martucci, Gianfranco; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: In recent years, health professionals’ education has moved towards the increasing use of blended learning. One of the most widespread blended formulas is the mix of face-to-face and online learning, which combines the advantages of distance learning, both in training provision and in training fruition, with the maintenance of socialization goals and application to practice activities. This literature review aims to find out whether blended-learning is employed for improving health professionals’ communication skills and which are its outcomes. Methods: Literature review of publications released from January 2000 to January 2019 was conducted across the academic databases Cinahl (EBSCO), Cochrane and Pubmed using relevant keywords. Results: Research has shown that blended learning is used in the education of different health professionals (students, nurses, physicians, etc.) at various stages of the educational path. The enhancement of communication skills appears to be a secondary learning objective in many studies, but it is shown to be nevertheless central to the proper acquisition and application of more clinical skills addressed by the blended courses. The blended modules here examined achieved their goals. However, the evaluation of the learning outcomes is still based on self-assessment, and thus needs to be implemented. Conclusions: Blended learning providers would need to pay more attention in the design and implementation phases of blended modules, assessing participants’ needs and offering more tailored and targeted programs, and should provide a more rigorous evaluation of learning outcomes.